2021
DOI: 10.1590/1983-40632021v5169594
|View full text |Cite
|
Sign up to set email alerts
|

Effect of shading screens on the production and quality of ‘Smooth Cayenne’ pineapple

Abstract: In pineapple cultivation, it is common to cover the fruit with newspaper, in order to avoid scalding caused by sunburn. However, the scarcity of material and the large labor force required have led to the search of control alternatives. This study aimed to evaluate the use of shading screens in the production and quality of ‘Smooth Cayenne’ pineapple. A randomized blocks experimental design was used, with five treatments (fruits covered with newspaper and plants covered with screens with 35, 40, 50 and 80 % of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…The use of shade netting in pineapple cultivation to protect fruits from sunburn due to high radiation and improve yield has been reported [19][20][21]. However, there are few studies reporting on the effect of shading or a lack of light [33] from planting to harvest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of shade netting in pineapple cultivation to protect fruits from sunburn due to high radiation and improve yield has been reported [19][20][21]. However, there are few studies reporting on the effect of shading or a lack of light [33] from planting to harvest.…”
Section: Discussionmentioning
confidence: 99%
“…In certain regions of pineapple cultivation, where sunlight is intense, the installation of shade netting after floral induction is common to prevent severe fruit sunburn and preserve quality [19,20]. Additionally, it has been reported that the use of shade nets increases pineapple crop productivity [21]. However, there is limited information on plant responses when shade netting is installed from the beginning of planting.…”
Section: Introductionmentioning
confidence: 99%